"When Women Do the Work of Men": Representations of Gendered Occupational Identities on British Railways in World War I Cartoons. (November 2019) - Robertson, Emma; Monk, Lee-Ann
Abstract : During World War I in Britain, women workers took on previously men-only jobs on the railways. In response to this wartime development, the National Union of Railwaymen published a series of cartoons in their journal, Railway Review. These images depicted women employed as porters and guards, occupying the engine footplate, and acting in the role of station-mistress. Through a close reading of the cartoons, and related images in the journal, this article examines how the humorous portrayal of female railway workers reinforced masculine occupational identities at the same time as revealing ambiguities in (and negotiating anxieties over) the gendered nature of railway employment. Despite wartime labour shortages, certain occupations, notably the driving and firing of steam trains, remained stolidly men's work and would do so until the late twentieth century. By scrutinising the construction of gendered occupational culture in union journals, we can better understand the tenacity of notions of "traditional" work for men and women on the railways.